Conflicts in Tourism Villages and their Settlement Mechanisms (Case Study in Bali, Yogyakarta, Subang, Indonesia) - Rahman Hamid, Abdul; Martini, Martini; Siswanto, Achmad; Riady, Yasir (IJBLE Scientific Publications Community Inc., 2023)
This article describes a map of potential conflicts and the mechanisms used to resolve conflicts in the best tourist villages in Indonesia, namely Panglipuran Bali, Nglanggeran Yogyakarta and Cisaat, West Java. The three villages were chosen by the researchers because they had different conflict characteristics and resolution mechanisms, so the coping strategies were also used in different ways. This study uses a qualitative approach with a case study method as a strategy of inquiry. The research subjects and locus were carried out among stakeholders, village tourism actors, local communities and tourists in the three villages which were the locus of this research. Data collection was carried out using in-depth interviews supported by extensive observation and document studies. The results of this study show that conflicts over the management of tourism objects in Panglipuran Bali can be overcome by using a customary institutional approach. Meanwhile, in Nglanggeran, Yogyakarta, the role of youth as actors is important in overcoming conflict. In Cisaat Village, efforts to resolve conflicts involve formal institutions such as the village administration.